Applying Harm Reduction Principles to the Work of Social Workers and “Equal – Equal” Peer Counsellors - Butvilas, Tomas; Petuškaitė, Aistė; Žibėnienė, Gintautė; Bubnys, Remigijus (Social Welfare: Interdisciplinary Approach, 2023)
This article presents a study on individuals who provide harm reduction services following the “Equal – Equal” principle – “Equal – Equal” consultants. Their activities are not regulated or extensively studied in Lithuania, but they are being implemented in practice. Both at the scientific and practical levels, there is a discussion about the effectiveness of “Equal – Equal” interventions, so it is likely that services provided on the “Equal – Equal” principle will be integrated into the system of assistance for individuals using psychoactive substances in the future. The study aimed to reveal how “Equal – Equal” consultants and one of the “traditional” harm reduction service providers – social workers – apply harm reduction principles when providing services to individuals using psychoactive substances. During the study, the “Equal – Equal” principle was revealed, harm reduction principles were identified, and the main similarities and differences in the application of harm reduction principles between professional service providers – social workers and “Equal – Equal” consultants were determined. The qualitative study found that collaboration with communities using psychoactive substances is not typical for the activities of social workers. This group is more inclined to focus on client abstinence, and there is a related moral judgment of the client. Social workers apply the principle of collaboration with the client on a broader scale than “Equal – Equal” consultants. The application of the autonomy principle in social work is complicated by the “double mandate dilemma.” “Equal – Equal” consultants view psychoactive substance use in a very pragmatic way, emphasizing problem-solving strategies based on humanism. Both groups prioritize client life and health protection, rely on an individual approach to the client, and experience difficulties due to emotionally driven desires to influence client decisions.